Estudo dos compostos fenólicos da casca de café orgânico: bioacessibilidade, bioatividades, influência de metabolitos na microbiota humana e proteção de células Caco-2 - Abreu, Thaianaly Leite (2023)
Coffee husks are the main by-product of the coffee industry and are generally discarded or used as fertilizer. The use of coffee husks can have environmental and social benefits, and when combined with the organic production of a more sustainable crop, these impacts are mitigated. This byproduct is increasingly being studied and used for its antioxidant, anti-inflammatory, anticoagulant, and antimicrobial properties, as well as its prebiotic potential. These effects are related to bioactive compounds such as phenols and fiber-bound macroantioxidants, which are able to reduce oxidative stress, regulate gene expression, protect body cells from ROS damage, and modulate the gut microbiome of people with diabetes. In view of the above, the aim of this study was to evaluate organic coffee husks in terms of their composition of phenolic compounds and macroantioxidants, their antioxidant capacity (DPPH, ABTS, ORAC and FRAP), their in vitro simulated digestion, bioavailability, anticoagulant effect, cytoprotective effects/cytotoxicity on Caco-2 cells (MTT and DCF-DA), in vitro intestinal fermentation with fecal inoculum of diabetic patients, in addition to flow cytometry and prebiotic index. The first study was based on the realization of three extracts, namely extractable polyphenols (EP), non- extractable hydrolyzable polyphenols (HNEP) and non-extractable polyphenols (NEP), which were characterized and evaluated for their bioactive properties after simulated gastrointestinal digestion. The results show that the transfer process affects the occurrence of polyphenols in coffee peels, especially for caffeic acid, gallic acid, and chlorogenic acid. The free and condensed polyphenols found in the extracts and undigested bark exhibited remarkable bioavailability and anticoagulant potential in addition to antioxidant properties against ABTS, FRAP, DPPH and ORAC radicals. The results of the second study showed good potential of the peel with antioxidant activity that significantly maintained the effect against all radicals under gastric conditions. The sample also showed cell vitality and developed in ROS in all studies. As for fecal fermentation, there was a positive change in the release of phenolic compounds in the presence of the bark. The positive prebiotic index was found for CH, while the negative prebiotic index was found for NC, indicating an overlap of bacteria to the detriment of bacteria during colonic fermentation. These results indicate the great potential of coffee husks as a source of bioactive compounds associated with important biological, cellular, and metabolic effects in maintaining the microbiota of individuals with diabetes because they have a disrupted intestinal barrier, and the byproduct may open new perspectives for food science and technology as a potential nutraceutical.